Strategies for Sourcing and Utilizing Working Capital to Improve Liquidity: A Case Study of PT Unilever Indonesia Tbk - Sri Yuningsih; Asri Sundari; Shofia Rofifah Azzhara; Azhar Eka Mustopa; Putri Pratiwi (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study analyzes changes in net working capital, activities affecting cash flow, and the liquidity position of PT Unilever Indonesia Tbk for 2024–2025. Research Method: This study employs a quantitative descriptive approach using case studies and comparative analysis of audited financial statements. The analysis covers net working capital, the current ratio, the quick ratio, the cash ratio, and cash flows from operating, investing, and financing activities. Results and Discussion: The net working capital deficit narrowed from Rp6.55 trillion to Rp3.68 trillion. The current ratio increased from 0.45 to 0.74; the quick ratio from 0.23 to 0.57; and the cash ratio from 0.06 to 0.40. The increase in cash was primarily related to operating cash flow and discontinued operations, rather than merely a decrease in accounts receivable and inventory. However, all ratios remained below 1.00, and tax liabilities increased materially. Implications: The company needs to integrate cash flow projections with the monitoring of liability maturities. Originality: This study integrates changes in working capital, liquidity ratios, cash flow, and liability composition in a two-period comparison.